Injection-related hepatitis C serosorting behaviors among people who inject drugs: An urban/rural comparison. Issue 4 (2nd October 2019) - Duncan, Ian; Habecker, Patrick; Hautala, Dane; Khan, Bilal; Dombrowski, Kirk
ABSTRACT: Although previous research has focused on injection drug use behaviors in both urban and rural settings, few have drawn direct comparisons between adjacent rural and urban areas. Using data from the National HIV Behavioral Surveillance study as well as original data collected in a similar fashion, we compare the risk behaviors of people who inject drugs (PWID) in San Juan, Puerto Rico, with those of PWID in nearby rural areas. Specifically, we examine whether one's own hepatitis C (HCV) infection status can be used to predict whether one asked their most recent co-injection partner about their HCV status. Acquiring such information allows injectors to seek out co-injection partners of concordant status as a way to minimize the risk of viral transmission. Results indicate that urban PWID with a known HCV+ status were more likely to know their last co-injector partner's HCV status than were their peers with a negative or unknown HCV status. However, this relationship was not present in the rural data. These findings suggest that there are different risk norms in rural and urban PWID communities and that interventions successful in one type of community may not be so in others.